UPAYA PENINGKATAN MINAT BACA AL QUR’AN PADA ANAK USIA 4-5 TAHUN MELALUI METODE IQRO DI SPS BOUGENVIL DESA MEKARSARI KECAMATAN CIRACAP - Kindar Pradina; Ibnu Hurri; Indra Zultiar (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Early childhood is a group of humans who are in the process of growth and development (Tatminingsih, 2019). This suggests that early childhood children are unique individuals who have specific patterns of physical, cognitive, socio- emotional, creativity, language and communication growth and development according to the stages the child is going through (Suryana, 2019:5). Firstly, to increase interest in reading the Koran in children aged 4-5 years through the iqro case study method at SPS Bougenvil, Mekarsari Village, Ciracap District. Second, to find out the iqro method at SPS Bougenvil, Mekarsari Village, Ciracap District. This research uses a qualitative method with a case study research design. The results of the research show that increasing interest in learning the Qur'an using the iqro method at SPS Bougenvil was planned before learning started and the implementation of reading the Qur'an using the iqro method at SPS Bougenvil, Mekarsari Village, Ciracap District, Sukabumi Regency was good because it was taught directly between teachers and students, learning is carried out using active student learning (CBSA) and teachers teach reading the Koran using the iqro method every day.